Lung Transplantation in Patients with High Lung Allocation Scores in the US: Evidence for the Need to Evaluate Score Specific Outcomes - Jeremiah A. Hayanga; Alena Lira; Tedi Vlahu; Jingyan Yang; Jonathan K. Aboagye; Heather K. Hayanga; James D. Luketich; Jonathan D’Cunha (Journal of Transplantation)
Objective. The lung allocation score (LAS) resulted in a lung transplantation (LT) selection process guided by clinical acuity. We sought to evaluate the relationship between LAS and outcomes. Methods. We analyzed Scientific Registry of Transplant Recipient (SRTR) data pertaining to recipients between 2005 and 2012. We stratified them into quartiles based on LAS and compared survival and predictors of mortality. Results. We identified 10,304 consecutive patients, comprising 2,576 in each LAS quartile (quartile 1 (26.3–35.5), quartile 2 (35.6–39.3), quartile 3 (39.4–48.6), and quartile 4 (48.7–95.7)). Survival after 30 days (96.9% versus 96.8% versus 96.0% versus 94.8%), 90 days (94.6% versus 93.7% versus 93.3% versus 90.9%), 1 year (87.2% versus 85.0% versus 84.8% versus 80.9%), and 5 years (55.4% versus 54.5% versus 52.5% versus 48.8%) was higher in the lower groups. There was a significantly higher 5-year mortality in the highest LAS group (HR 1.13, p=0.030, HR 1.17, p=0.01, and HR 1.17, p=0.02) comparing quartiles 2, 3, and 4, respectively, to quartile 1. Conclusion. Overall, outcomes in recipients with higher LAS are worse than those in patients with lower LAS. These data should inform more individualized evidence-based discussion during pretransplant counseling.